Market entry modes of Icelandic fisheries companies - Óskar Gunnarsson 1987- (2016)
The aim of this research is to study the market entry modes of Icelandic fisheries companies that are exporting marine goods to the United States via Boston. A market entry model which consists of various influencing factors will be used to assess the market environment. The results from the model will then be compared with the current export methods of the companies. This research also seeks to gain an understanding of how the companies carry out their expansion into foreign markets. The literature covers internationalization theories as well as theories on market entry strategy and market entry modes. It explores how market entry methods have developed through the years and explains the importance of choosing the right entry mode when entering foreign markets. The model used in this research is explained thoroughly, and all the influencing factors as well. This study is based on qualitative interviews conducted with fisheries companies in Iceland and importers of seafood located in Boston. In addition, quantitative data was collected in order to get a more comprehensive overview of the market. The collected data was then used to find an ideal market entry mode, using the market entry model. The results indicate that intermediate entry modes, such as joint ventures are fitting for these companies in the United States market. The results also suggest that if the market entry model is to be used in a practical way, it will have to be adjusted accordingly. Keywords: market entry modes, fisheries companies, exports, entry model